2015
DOI: 10.1002/geot.201500024
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term deformation of mountain tunnel lining and ground under swelling rock condition

Abstract: To monitor deformation in a road tunnel in service, periodical inspections are performed and countermeasures are taken as needed. Cracking of the permanent lining and heaving of the road surface often occur, however, so it is difficult to assess the development of such deformation features from data acquired during the construction and service stages. In this paper, the deformation mechanism and the effect of countermeasures are discussed based on the results of in situ measurements over a six‐year period and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Vertical displacements were fixed at the top and horizontal displacements were fixed at both sides. The loading direction is supposed to act upwards to simulate heaving, based on a previous study (Isago et al, 2015). Figure 6 shows the cross-sections of the lining model in the actual scale analysis.…”
Section: Actual Scale Analysismentioning
confidence: 99%
“…Vertical displacements were fixed at the top and horizontal displacements were fixed at both sides. The loading direction is supposed to act upwards to simulate heaving, based on a previous study (Isago et al, 2015). Figure 6 shows the cross-sections of the lining model in the actual scale analysis.…”
Section: Actual Scale Analysismentioning
confidence: 99%
“…During the tunnel excavation of the Trasvasur tunnels (Canary Islands, Spain) (Pérez-Romero et al, 2007), found that it is advisable to seal off the excavation as soon as possible to prevent change due to the decompression of the swelling clay levels and the absorption of water from the tunnel itself. Researching the deformation mechanism of swelling rock (Zhang et al, 2021b;Isago et al, 2015;Oldecop and Alonso, 2012), it was found that these measures that was the implementation of bolts (Waldemar 2015; Jeong et al, 2015), reinforced linings (Li et al, 2019;Bilir and Sarıgül, 2021;Korzeniowski et al, 2015), allowable deformation to reduce expansion pressure measurement (Aksoy et al, 2012;Sun and Wang, 2011) and so on can greatly reduce the probability of large deformation of the tunnel. Currently, most of the research on the stability of the tunnel is focused on the deformation of the surrounding rock in the process of construction, while the research on secondary lining failure during tunnel operation is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Composite structures made of concrete–concrete, concrete–rock, or rock–rock are widely found in civil engineering, such as in underground constructions, 1,2 tunnels, 3 and lined rock caverns (LRC) 4–6 . During their serving periods, these civil structures are inevitably subjected to the comprehensive effects of environmental erosions (such as high temperatures, freezing, and thawing), impact geo‐pressure, engineering disturbances (blasting, digging, etc.…”
Section: Introductionmentioning
confidence: 99%